2023
DOI: 10.1007/s13181-023-00933-7
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Suspected Suicides and Nonfatal Suicide Attempts Reported to United States Poison Control Centers Before and During the COVID-19 Pandemic

Abstract: Introduction This study investigated the characteristics and compared the trends of pediatric suspected suicide and nonfatal suicide attempts reported to United States (US) poison control centers (PCCs) before and during the first year of the COVID-19 pandemic. Methods An interrupted time series analysis using an ARIMA model was conducted to evaluate the trends of suspected suicides and nonfatal suicide attempts among children 6–19 years old reported to the National Poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…The most likely explanation is the change in the healthcare system utilization in this peculiar time period, in Italy and many other countries, 28–30 presumably related to fear of exposure to the virus and to the restriction measures adopted. Also consistent is the increase of cases back to pre‐pandemic levels in the following months, identified in our data as starting in the first trimester of 2021, whereas other authors reported slightly earlier resumptions 21,22 . When subdividing our cases of interest in single‐ and multi‐agent cases, though, single‐agent self‐harm poisonings showed a linear increase after year 2020, with a peak in 2022 above pre‐pandemic levels (Table 1).…”
Section: Discussionsupporting
confidence: 88%
“…The most likely explanation is the change in the healthcare system utilization in this peculiar time period, in Italy and many other countries, 28–30 presumably related to fear of exposure to the virus and to the restriction measures adopted. Also consistent is the increase of cases back to pre‐pandemic levels in the following months, identified in our data as starting in the first trimester of 2021, whereas other authors reported slightly earlier resumptions 21,22 . When subdividing our cases of interest in single‐ and multi‐agent cases, though, single‐agent self‐harm poisonings showed a linear increase after year 2020, with a peak in 2022 above pre‐pandemic levels (Table 1).…”
Section: Discussionsupporting
confidence: 88%
“…They have also reported that the incidence rate increase was higher among females and increased faster in mid-adolescence patients. Worryingly, during the three years of the COVID-19 pandemic (2019–2021), the number of suicide attempts by children and adolescents up to 18 years of age increased [ 37 ] along with an upward longitudinal trend of acute psychopathological symptoms, including depression, post-traumatic-stress disorder, and psychosis [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians can use these data to increase efforts to screen their pediatric patients for mental health problems using a variety of screening techniques to identify problems early in childhood and/or adolescence. Sensitive topics can be screened and dealt with as well, including suicidality, substance abuse, and gender identity . Clinicians, researchers, and parents are all in the same exciting and fascinating journey seeking to understand the mental health of children and learning to help them as much as possible for their overall maximal health as they experience life in this challenging 21st century.…”
mentioning
confidence: 99%
“…Sensitive topics can be screened and dealt with as well, including suicidality, substance abuse, and gender identity. 1,[5][6][7][8][9][10] Clinicians, researchers, and parents are all in the same exciting and fascinating journey seeking to understand the mental health of children and learning to help them as much as possible for their overall maximal health as they experience life in this challenging 21st century. There is much clinicians can do for these parents and children; the encouragement and guidance from these respected researchers is greatly appreciated.…”
mentioning
confidence: 99%
See 1 more Smart Citation